2017
DOI: 10.1002/cpp.2145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the paths between dysfunctional attitudes towards motherhood and postpartum depressive symptoms: The moderating role of self‐compassion

Abstract: Better understanding how cognitive processes operate to influence women's depressive symptoms during the postpartum period is crucial for informing preventive and treatment approaches. The present study aimed to examine the relationship between women's dysfunctional attitudes towards motherhood and depressive symptoms, considering the mediating role of negative automatic thoughts and the moderating role of self-compassion. A sample of 387 women in the postpartum period cross-sectionally answered a set of quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
3
9
1
1
Order By: Relevance
“…First, our results show that more dysfunctional beliefs toward motherhood related with others’ judgments and with maternal responsibility were associated not only with higher depressive symptoms, congruently with prior research (Fonseca & Canavarro, ; Sockol et al., ; Wittkowski et al., ), but also with higher anxiety symptoms, suggesting that dysfunctional beliefs toward motherhood may be conceptualized as a broad cognitive vulnerability for postpartum psychological disorders (anxiety and depression) and not only for postpartum depression. Dysfunctional beliefs related to maternal responsibility and to the judgment of others seem to have underpinned the self‐imposed high standards of performance (the myth of perfect motherhood ) in the maternal role (Blissett & Farrow, ), which may translate into the women's conditioning of their personal value as a mother to their performance and the fear of failure and of others’ criticisms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, our results show that more dysfunctional beliefs toward motherhood related with others’ judgments and with maternal responsibility were associated not only with higher depressive symptoms, congruently with prior research (Fonseca & Canavarro, ; Sockol et al., ; Wittkowski et al., ), but also with higher anxiety symptoms, suggesting that dysfunctional beliefs toward motherhood may be conceptualized as a broad cognitive vulnerability for postpartum psychological disorders (anxiety and depression) and not only for postpartum depression. Dysfunctional beliefs related to maternal responsibility and to the judgment of others seem to have underpinned the self‐imposed high standards of performance (the myth of perfect motherhood ) in the maternal role (Blissett & Farrow, ), which may translate into the women's conditioning of their personal value as a mother to their performance and the fear of failure and of others’ criticisms.…”
Section: Discussionsupporting
confidence: 90%
“…In the postpartum context, when women self‐impose high standards in their maternal performance (i.e., have more dysfunctional beliefs related with maternal responsibility and others’ judgments), they may present with more frequent postpartum‐specific negative automatic thoughts (Fonseca & Canavarro, ) and negative emotions, which they may have greater difficulties in accepting, and increase their tendency to engage in experiential avoidance strategies. These experiential avoidance strategies are intentional strategies to diminish or extinguish painful private experiences (e.g., negative thoughts) with which they are unwilling to cope (Hayes et al., ; Hayes et al., ), and may include strategies, such as rumination (as a way to realize why the person is thinking and feeling in a negative way; Barnum et al., ), or behavioral avoidance of activities that may lead to negative thoughts and feelings (e.g., avoidance of new experiences with the baby, by fearing that something might go wrong).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater women’s ability to enhance such skills in the postpartum period, the greater their ability to deal with the private negative experiences (emotions and thoughts) associated with their parenting experience by being more aware and accepting of such emotions and by using more adaptive emotion regulation strategies (Haga et al, 2012). These women may also be able to adopt a kinder and more self-compassionate attitude toward their own experiences (Felder et al, 2016; Fonseca and Canavarro, 2018), which may help them to better address the unrealistic expectations of “perfect motherhood,” accept their vulnerable and human nature and be less judgmental toward themselves in the presence of motherhood-related negative experiences, both external and internal (e.g., thoughts/emotions) (Fonseca and Canavarro, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the role of self-compassion, understood as the individual’s ability to have a kind and caring attitude toward oneself in the face of personal inadequacies or suffering while acknowledging that all individuals share a common human condition (Neff, 2009, 2012), has also been highlighted. Lower levels of self-compassion were found to be associated with higher levels of postpartum depressive symptoms (Felder et al, 2016; Fonseca and Canavarro, 2018), and Cohen (2010) found that greater self-compassion during pregnancy can exert a protective effect on the development of postpartum depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%